Culturally Responsive Pedagogy (CRP) in Multicultural Classrooms: A Convergent Mixed-Methods Study in Malaka Regency, East Nusa Tenggara - Susilo Setyo Utomo; Djakariah; Muhammad Husain Hasan; Loso Judijanto; Akhlaqur Rahman (Faculty of Educational Sciences, UIN (State Islamic University) Syarif Hidayatullah Jakarta, 2026)
Existing studies on Culturally Responsive Pedagogy (CRP) tend to focus primarily on teachers’ instructional practices, with limited attention to the simultaneous examination of both teachers’ and students’ understanding, particularly in remote and culturally diverse regions. This study aims to analyze the level of understanding and implementation of CRP among senior high school teachers and students in East Nusa Tenggara, Indonesia. A convergent mixed-methods design was employed. Quantitative data were collected through a structured CRP questionnaire administered to students, while qualitative data were obtained through in-depth interviews with three teachers. Data were analyzed using descriptive statistics and thematic analysis supported by NVivo software. The findings indicate that most students demonstrate an advanced level of understanding of CRP principles. Teachers exhibited varying levels of competence, with one teacher reaching an exemplary level in curriculum integration and structural inequity prevention. These results suggest that CRP implementation in East Nusa Tenggara has progressed significantly; however, sustained institutional support and deeper critical reflection remain necessary to achieve systemic and long-term impact.